2013
DOI: 10.1111/ajop.12048
|View full text |Cite
|
Sign up to set email alerts
|

Political violence, health, and coping among Palestinian women in the West Bank.

Abstract: Political violence poses a considerable threat to the health of individuals. Protective factors, however, may help people to build resilience in the face of political violence. This study examined the influence of lifetime and past 30‐day experiences of political violence on the mental and physical health of adult Palestinian women from the West Bank (N = 122). Two hypotheses were examined: (a) Reports of political violence exposure would be related to reports of poorer physical and mental health and (b) sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 112 publications
(163 reference statements)
2
27
0
Order By: Relevance
“…Religion was also associated with a lower probability of having a mental health condition in women. Engaging in religious activities and receiving advice from religious groups have previously been shown to be protective against poor mental health in other conflict-affected populations (Ruwanpura et al 2006 ; Hardgrove, 2009 ; Sousa, 2013 ; Seguin & Roberts, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Religion was also associated with a lower probability of having a mental health condition in women. Engaging in religious activities and receiving advice from religious groups have previously been shown to be protective against poor mental health in other conflict-affected populations (Ruwanpura et al 2006 ; Hardgrove, 2009 ; Sousa, 2013 ; Seguin & Roberts, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, limited research exists examining the potential association between self-reliance and more negative outcomes after stress and trauma, such as PTSS severity. Although not directly assessing PTSS severity, Sousa [ 26 ] found that higher levels of self-reliance were associated with more negative effects of political violence on physical and mental health in a sample of adult Palestinian women from the West Bank. Among adolescents in the U.S., youths endorsing extremely high levels of self-reliance reported significantly higher symptoms of depression and suicidal ideation compared to individuals reporting lower levels of self-reliance [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The whole Palestine region, and the Gaza Strip in particular, have undergone persistent conflict for decades, implying repetitive exposure to violence and war, and clearly affecting the psychological state and health of the population, and the quality of their life (Thabet, Abed, & Vostanis, 2001; Thabet & Thabet, 2016), adding urgency to the need to understand and address the implications of war-related trauma among this population. Recently, several studies have noted the psychopathological consequences of war in the Gaza Strip among adult women (Sousa, 2013), adolescents (Thabet, El-Buhaisi, & Vostanis, 2014), and preschool children (Thabet, Abu-Khusah, & Vostanis, 2014) and have assessed the memories of traumatic events among adults (Manzanero, López, Aróztegui, & El-Astal, 2015).…”
Section: Introductionmentioning
confidence: 99%